Analysis of Village Government Financial Management Performance in Aceh - sufitrayati sufitrayati; Mirna Indriani; Mukhlis Mukhlis; Syukriy Abdullah (International Journal of Artificial Intelligence Research, 2022)
The purpose of this research is to find out how the influence of the independent variable (Human Resource Competence Variable, Infrastructure Variable and Income Source Variable) on the dependent variable (Financial Management Performance) through the mediating variable (organizational commitment). This research is located in Aceh Province. The population in this study are individuals who are involved in preparing village financial accountability reports, these individuals are spread across 23 districts/cities in the Aceh Province government, these individuals consist of the Treasurer, Secretary, and Village Head. The sampling technique used in this study is the proportional sample technique. The number of samples involved in this study were 87 respondents. The results of this study indicate that; (1) Human Resources Competence has an effect on Financial Report Accountability. (2) Infrastructure affects the Accountability of Financial Statements. (3) Sources of Income affect the Accountability of Financial Statements. (4) Human Resource Competence has an effect on Financial Management Performance. (5) Infrastructure has no effect on Financial Management Performance. (6) Source of Income has an effect on Financial Management Performance. (7) Financial Statement Accountability has an effect on Financial Management Performance. (8) Financial Statement Accountability has no influence in mediating Human Resource Competence on Financial Manager Performance. (9) Financial Report Accountability has an influence in mediating Infrastructure on the Performance of Financial Managers. (10) Accountability of Financial Statements has an influence in mediating sources of income on the performance of financial managers